Analysis of an archery bow using finite element method and the development of an arcery bow - Sharveenesh, Vathivellu (2013)
In terms of Archer, it has been a well known sport worldwide. Basically, a bow consists of 3 main parts which is the riser, limb and the string. In improving the performance of the bow, it is crucial to research each and every part of the bow. There are many mathematical modelling has been done to improve the performance of the bow but only few analysis and experiments are done. Therefore, the objective of the study is to analyse the Archery Bow using Finite Element Method and to develop the Archery Bow. Two different methods were used before fabricating the bow which is to analyse the stress and strain of the bow drawn in CAD software using FEM software and to test experimentally using the strain gauge method. Validation between the results was used as a reference for fabrication. The best material was chosen by doing a simulation analysis on the composite materials which shows that E fibreglass have the best properties compared to the other fibreglass. Therefore, as for the results, E fibreglass is used to fabricate the limb of the bow so that it will be highly in strength and also in elasticity which is up to 72.4 GPa. The results shows that the fabricated bow have a lower strain which are 0.00244 compared to the current bow which is 0.004694. This shows that the fabricated bow have a higher potential to withstand much higher force compared to the current bow which makes the new bow to have a better quality. As for the error analysis, it shows that the higher force applied to the bows makes the error to increase to the increase in vibration and the damping force.